Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/polb.10357
|View full text |Cite
|
Sign up to set email alerts
|

Carbon black‐filled polyolefins as positive temperature coefficient materials: The effect ofin situgrafting during melt compounding

Abstract: For the production of polymer-based conducting composites serving as positive temperature coefficient (PTC) materials with lower room-temperature resistivity and sufficiently high PTC intensity, carbon black has been pretreated with acrylic acid and some initiator and then melt-mixed with low-density polyethylene. Because of the in situ formation of covalent bonding at the filler/matrix interface, the distribution status and thermally induced displacement habit of the conductive fillers have changed accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The higher is the grafting monomer dosage, the higher the grafting percentage is, demonstrating the appropriateness of the calculation of φ g1 and φ g2 . Considering the results of FTIR–ATR, as well as X‐ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (FTIR–TGA) measurements reported in our previous paper,21 it is believable that the grafting monomer is grafted onto the CB surface. Moreover, it is understood from Table I that even if the dosage of grafting monomer is same, the grafting percentages vary with the types of the monomers, and AA gives the highest grafting percentage.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The higher is the grafting monomer dosage, the higher the grafting percentage is, demonstrating the appropriateness of the calculation of φ g1 and φ g2 . Considering the results of FTIR–ATR, as well as X‐ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (FTIR–TGA) measurements reported in our previous paper,21 it is believable that the grafting monomer is grafted onto the CB surface. Moreover, it is understood from Table I that even if the dosage of grafting monomer is same, the grafting percentages vary with the types of the monomers, and AA gives the highest grafting percentage.…”
Section: Resultsmentioning
confidence: 90%
“…It is assumed that the presence of direct bridging chain, a single chain adsorbed on two separate aggregate, is responsible for the appearance of the plateau. In our previous study,21 we obtained in situ melt‐grafted‐CB filled LDPE composites and studied the electrical properties of the composites. In the present article, we pay our attention to the effect of different species of grafting monomers on the viscoelastic behavior of the composites at both melt and solid state.…”
Section: Introductionmentioning
confidence: 99%
“…8 shows the plots of DC resistivity (reciproal of DC conductivity) against temperature for HDPE/PS/1.1 vol% CNF composite, normalized to its corresponding value at 25 °C. The resistivity remains almost unchanged at low temperatures (< 40 °C), and thereafter increases rapidly with increasing temperature, showing a positive temperature coefficient effect at temperature above 115 ºC [14][15][16][17][18]. This effect arises from the macromolecular segments begining to relax as the testing temperature is increased, leading to the disruption of percolating CNF paths embedded within polymer matrix.…”
Section: Electrical Behaviormentioning
confidence: 99%
“…However, a great disadvantage associated with a sharp negative temperature coefficient (NTC) effect in CB filled semicrystalline polymer composites limits their application in over‐temperature protections 12. Crosslinking of the semicrystalline polymer matrix by peroxide, gamma radiation, or electron beam has been reported to eliminate the NTC effect 13, 14. Chan et al15, 16 have reported that presence of very high molecular weight PE in (UHMWPE–CB) and (UHMWPE–PP–CB) composites could eliminate the NTC effect even though they were not crosslinked.…”
Section: Introductionmentioning
confidence: 99%